1976
DOI: 10.1084/jem.143.1.167
|View full text |Cite
|
Sign up to set email alerts
|

Lymphopoiesis and lymphocyte recirculation in the sheep fetus.

Abstract: The production and the circulation of lymphocytes has been examined in the sheep fetus where neither foreign antigen nor immunoglobulins occur. It was found that as the lymphoid organs increased in size during fetal life, the numbers and the output of lymphocytes in the thoracic duct lymph increased. The recirculating pool of lymphocytes was estimated to be 5.5 +/- 1.5 X 10(8) cells in fetal lambs 95-100 days of age, 5.7 +/- 1.2 X 10(9) cells in fetuses 130-135 days of age, and 1.2 +/0 9.3 X 10(10) cells in fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1976
1976
2006
2006

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…The general aspects of surgery on fetal sheep were similar to previous descriptions. 15,16 At 63 days of gestation the fetus was exposed by Caesarean section under thiopentone and halothane anaesthesia. The fetus received a single intraperitoneal injection of a monoclonal antibody directed against sheep IgM (McM9).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…The general aspects of surgery on fetal sheep were similar to previous descriptions. 15,16 At 63 days of gestation the fetus was exposed by Caesarean section under thiopentone and halothane anaesthesia. The fetus received a single intraperitoneal injection of a monoclonal antibody directed against sheep IgM (McM9).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Immunological studies have shown essentially the same pattern of development for thymus, spleen and lymph nodes (LN) in both species [8]. In addition, the sheep fetus (by means of a syndesmochorial placenta) remains immunologically naive until birth [9,10]. The thymus in sheep, like humans, is colonized in the first third of gestation [10,11], and reaches its maximum size as a percentage of body weight at 120 days of gestation [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the rate of loss of cells from foetal prescapular lymph nodes often exceeded e.stimates of the rate at which lymphocytes are added to the recirculating pool of cells based on data from thoracic duct cannulation in foetal lambs (Pearson et al, 1976). This probably accounts for the exponential fall in the output of lymphocytes during drainage from unchallenged prescapular lymph nodes.…”
Section: Effects Of Blockages Of Major Lymphatics In Foetal Lambsmentioning
confidence: 99%